The determinants of firm profitability in the Tunisian Stock Exchange - Ben Moussa, Mohamed Aymen; Boubaker, Adel (Accounting Department,, 2023)
Purpose — This research aims to analyze the determinants of firm profitability in the Tunisian Stock Exchange. Design/methodology/approach—This research used a panel static model on a sample of 30 firms listed on the Tunisian stock exchange from 2016 to 2021. Findings — The results show that capital, size, liquidity, and economic growth positively affect firm profitability, but inflation and financial autonomy negatively affect firm profitability. Practical implications—This scholarly article's practical implications are that organizations can improve their profitability by focusing on capital, size, liquidity, and economic growth while also being cautious about inflation and financial autonomy. Originality/value — This scholarly article's original value lies in examining the determinants of firm profitability in the context of Tunisian stock exchange-listed firms. It provides insights into the specific factors that influence profitability and their effects. Paper type — Case research